Spatial disparities in zero-dose vaccination coverage for children aged 12–23 months in Ethiopia: A geographically weighted regression analysis - Berhanu Fikadie Endehabtu; Kassahun Alemu; Shegaw Angaw Mengiste; Mesert Zelalem; Monika Knudsen Gullslett; Biniyam Tilahun (PLoS ONE, 2025)
Background Though Ethiopia has made significant progress in childhood vaccination, many children remain unvaccinated, making it the third largest contributor to the global burden of zero-dose children. Zero-dose children are those who doesn’t receive the first dose of diphtheria, tetanus and pertussis containing vaccine. Identifying geographic inequities of zero-dose prevalence and the factors influencing it could help to effectively reach and identify at-risk children and to design tailored intervention. Objectives This study aimed to assess the geographical inequities and predicting factors of zero-dose children aged 12–23 month in Ethiopia. Methods We used a population-based survey data. A total of 6,212 children aged 12–23 were included. The spatial autocorrelation was employed to examine geographic variations in zero-dose children. Getis-Ord Gi* statistics was used for hotspot analyses. A Kriging interpolation technique used to estimate values of zero-dose at unmeasured locations based on known values of zero-dose at observed locations. The Geographic Weighted Regression (GWR) analysis was used to elicit determinants of geographic difference in zero-dose children. Adjusted R2 and Akaike Information Criteria (AICc) were used to compare the models. Results The prevalence of zero-dose children was 24.8% [CI: 23.7%−25.8%] ranged from 0.9% in Addis Ababa to 40.7% in Somali region. The zero-dose prevalence varied across the study area (Moran’s I = 0.193; P-value<0.0001). Significantly higher proportions of zero doses (hotspot areas) were identified in the north and south Somali, northwest Afar, East Amhara, and southern Oromia regions. GWR analysis showed that no ANC utilization, no TT/Td vaccination, poor perceptions on immunization, and far distance to healthcare facilities contributed to these geographic variations. Conclusion This study revealed that the prevalence of Zero-dose is unacceptably high, with geographic inequities varying across the country. Factors such as ANC utilization, TT/Td vaccination, perceptions of immunization, and distance to healthcare facilities contributed to these geographic differences. This underscores the importance of designing and implementing tailored interventions to identify and reach zero-dose children. Such an approach could help achieve the national and global immunization goal of leaving no one behind by providing equitable access to immunization.